Influence of trapezoidal tube parameters on electrical and thermal performance of hybrid photovoltaic solar panels integrated with phase change materials - Mohamed A. Alnakeeb; Mohamed A. Abdel Salam; Mohamed A. Hassab; Wael M. El-Maghlany (Case Studies in Thermal Engineering)
The photovoltaic-thermal hybrid system with phase-change material is designed to provide simultaneous thermal and electrical power output. In this paper, a detailed two-dimensional modelling of a photovoltaic thermal using phase change material is performed. The system utilizes water as the heat transfer fluid, which flows through a uniquely designed trapezoidal inner tube. This configuration is explored to enhance heat transfer and overall system efficiency. The model is numerically solved using ANSYS Fluent 19.2 to analyse the performance characteristics. The numerical analysis investigates the performance characteristics of the photovoltaic thermal technology combined with phase change material system across various aspect ratios (0.25, 0.5, 1, 1.5, and 2) and heights (3, 6, and 9 mm), marking a novel exploration into optimizing these parameters for enhanced energy efficiency. The phase change material melting is simulated by employing the enthalpy-porosity method. The validation of the numerical technique is confirmed by comparing the current study's results to the outcomes of the previous experimental study. Based on the findings, the overall efficiency improves as the aspect ratio and height increase. Among all simulated cases, the highest overall efficiency is attained with aspect ratio of 2 and a height of 9 mm, with a value of 70.1 %.